ANALYSIS OF INTERCULTURAL YOUTH BY THE EXAMPLE OF RUSSIAN AND AMERICAN INTERNET USERS - M. V. Sinyutin; R. D. Akinina; A. S. Gonashvili; A. O. Ivanova; D. A. Hannolaynen (Концепт: философия, религия, культура, 2017)
In this paper, the authors consider the problem of intercultural communication on the example of comparison of images of self-presentation of Russian and American youth who use social networks “Vkontakte” and “Facebook”. The authors, jn the basis of the idea of double contingently and unity of information, namely the communication and understanding that is used in the theory of Nicholas Luhmann, conducted the survey. In this study, by analyzing public information on personal pages of users in social networks “Vkontakte” and “Facebook”, an atterupt was wade to identify the methods and forms of constructing identity of Russian and American social media users. The article compares and assesses the information that these users post on their personal pages in social networks. In the study the authors come to the couclision that American users are more dynamic and open in communication than Russian users, however, both groups of users from Russia and from America have been trying to build a positive social image of themselves on the Internet. The article has a theoretical and applied nature, and it will be relevant for researchers studying sociology of youth and intercultural communication.